CHALLENGES FACED BY NURSING STUDENTS IN ONLINE EDUCATION DURING THE COVID-19 PANDEMIC - FARID, B; ZAFAR, M; RASHEED, K; ARSHAD, H (Biological and Clinical Sciences Research Journal, 2024)
Amid the COVID-19 pandemic, the transition to online education has posed significant challenges for nursing students worldwide. This study explores the multifaceted obstacles encountered during this shift and aims to provide insights for improving online nursing education. Utilizing a descriptive cross-sectional quantitative research design, data was collected from 73 final-year nursing students at Saida Waheed FMH College of Nursing, Lahore, using a structured questionnaire. The questionnaire assessed various domains, including learning effectiveness, software proficiency, instructor support, communication, course design, and psychosocial experiences. The results revealed a spectrum of student experiences, ranging from perceived benefits to substantial challenges adapting to online learning. While some students reported proficiency in online education tools, others faced difficulties navigating technology and accessing course materials. Instructor support emerged as a critical factor influencing students' satisfaction and learning outcomes, with clear communication and timely feedback paramount. Additionally, challenges related to course design and psychosocial experiences significantly impacted students' engagement and motivation. By comparing these findings with previous research, common themes and areas for improvement in online nursing education were identified. The study underscores the importance of targeted interventions to address technological barriers, enhance instructional support, optimize course design, and prioritize students' psychosocial well-being in online learning environments. Ultimately, these insights can inform the development of effective strategies to enhance the quality and effectiveness of online nursing education programs.